2018
DOI: 10.1002/jcb.28125
|View full text |Cite
|
Sign up to set email alerts
|

miR‐452 promotes cell metastasis and the epithelial to mesenchymal by targeting SOX7 in clear‐cell renal‐cell carcinoma

Abstract: Clear‐cell renal‐cell carcinoma (ccRCC) is the most common renal cell carcinoma (RCC), representing 75%‐80% of the cases of RCC, and characterized by a high recurrence rate and poor prognosis. miR‐452 acts as a tumor promoter in several tumors, including ccRCC. The purpose of this study was to determine the role of miR‐452 in ccRCC. miR‐452 and SOX7 messenger RNA and protein levels were calculated by quantitative reverse transcription polymerase chain reaction and Western blot analysis. MTT and Transwell assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…4E ), suggesting that Sox7 deficiency in the endocardium did affect ECM formation. Since proliferation contributes to EndMT and Sox7 is an important regulator of cell proliferation 21 , we examined the effect of Sox7 inactivation on proliferation of endocardial cells using immunofluorescence, and found that the number of KI67-positive endocardial cells in Nfatc1 Cre;Sox7 fl/fl cushions decreased sharply compared with those in controls (Fig. 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…4E ), suggesting that Sox7 deficiency in the endocardium did affect ECM formation. Since proliferation contributes to EndMT and Sox7 is an important regulator of cell proliferation 21 , we examined the effect of Sox7 inactivation on proliferation of endocardial cells using immunofluorescence, and found that the number of KI67-positive endocardial cells in Nfatc1 Cre;Sox7 fl/fl cushions decreased sharply compared with those in controls (Fig. 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…miR-452 is an evolutionarily conserved microRNA, which has been implicated in a variety of human cancers, including gliomas, colorectal cancer, non-small cell lung cancer, and prostate cancer 41 - 44 . In kidneys, Liu et al showed that miR-452 was up-regulated in clear-cell renal-cell carcinoma where it may promote cell proliferation and invasion by targeting SOX7, contributing to a poor 5-year survival in renal cancer patients 45 . This observation was verified by Zhai et al , although miR-452 was suggested to target SMAD4/SMAD7 signaling 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Among all these key DEMs, miR-21 ( Fritz et al, 2014 ), miR-34a ( Fritz et al, 2015 ), miR-124 ( Butz et al, 2015 ), miR-141 ( Liep et al, 2016 ), miR-146a ( Yang et al, 2018 ), miR-155 ( Zhang et al, 2018 ), miR-200c ( Jiang et al, 2016 ), miR-210 ( Samaan et al, 2015 ), miR-224 ( Fujii et al, 2017 ), miR-452 ( Liu et al, 2018 ) and miR-142 ( Liu et al, 2010 ) have been reported to be correlated with ccRCC. Therefore, our findings are consistent with those from former studies.…”
Section: Discussionmentioning
confidence: 99%